2018
DOI: 10.1002/smi.2834
|View full text |Cite
|
Sign up to set email alerts
|

A sample validation of the Adolescent Stress Questionnaire (ASQ) in New Zealand

Abstract: The Adolescent Stress Questionnaire (ASQ) is a 56-item scale measuring stress in 10 domains. The scale has been tested in a number of countries worldwide with mixed support. The current study tested the factor structure, construct validity, and reliability in a sample (n = 1,601) comprising a general population of adolescents in New Zealand. Support was found for the 10-factor structure with adequate internal consistency as well as strong factorial invariance between male and female participants. Significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Thus, it is plausible that cultural differences explain the reported results. Similar problems with the scale of Stress of Romantic Relationship were also demonstrated in another validation study by Sotardi and Watson (2019) for the 56-item version of the ASQ from New Zealand. Moreover, these authors also reported cross-loadings of items from scales of School Performance, Teacher Interaction, and School Attendance which underline the plausibility that sources of stress experienced by adolescents in different school domains are closely related to each other.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, it is plausible that cultural differences explain the reported results. Similar problems with the scale of Stress of Romantic Relationship were also demonstrated in another validation study by Sotardi and Watson (2019) for the 56-item version of the ASQ from New Zealand. Moreover, these authors also reported cross-loadings of items from scales of School Performance, Teacher Interaction, and School Attendance which underline the plausibility that sources of stress experienced by adolescents in different school domains are closely related to each other.…”
Section: Discussionsupporting
confidence: 70%
“…The results regarding the psychometric properties are mixed. While studies from Australia (Byrne et al, 2007), Greece (Darviri et al, 2014), New Zealand (Sotardi and Watson, 2019), Spain (Lima et al, 2017), and Turkey (Tanış, 2019) were able to show that the factor structure fits well for the long version, there are other studies that raise remarkable concerns regarding the structural validity and internal consistency (Moksnes and Espnes, 2011), test-retest reliability (De Vriendt et al, 2011), and problematic factor loadings of the ASQ (McKay et al, 2016). However, the majority of the previous work describes it as a valid and reliable instrument of stress measurement, and one which also seems to work in different cultures.…”
Section: Introductionmentioning
confidence: 99%
“…-653 of you'). Full details about measurement validation for the ASQ with a New Zealand population are reported elsewhere (Sotardi & Watson, 2019).…”
Section: Adolescent Stressmentioning
confidence: 99%
“…Furthermore, such tool should consider the modern factors of stress, such as job migration, isolation and loneliness, declining social trust, addiction to industrial drugs, neighborhood problems, and economic crisis. In addition, the necessity for making a tool to measure stressful events in our country comes from the fact that existing tools that are mainly developed in Western societies (15)(16)(17)(18)(19) are tailored to meet the needs of those societies. However, the tool in our study was developed by investigating other tools and solving their deficiencies, and also by paying attention to the structure and socio-economic status of Tehran metropolis.…”
mentioning
confidence: 99%
“…Valerie et al (18) and McKay ( 22) examined the reliability and validity of the Adolescent Stress Questionnaire (ASQ). Their results showed that the ASQ was a reliable, valid instrument for adolescent stress.…”
mentioning
confidence: 99%